2021
DOI: 10.1111/jpn.13661
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus equivalency of phytase with various evaluation indicators of duck in starter

Abstract: This study was conducted to evaluate phosphorus (P) equivalency of phytase with various evaluation indicators of ducks in starter (0–14 days). Three hundred and twenty 1‐day‐old Cherry Valley ducks were randomly assigned to eight groups. The dietary treatments were four levels of available phosphorus (aP) with 0.25%, 0.32%, 0.39%, and 0.46% (treatments I–IV) and four levels of phytase added to low‐aP basal diet (treatment I) with 300, 600, 900, and 1200 units (U) per kg (treatments V–VIII). The results were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, there has been no attempt to estimate the digestible Ca equivalency of phytase relative to limestone in broiler chickens, which might be partly due to the seeming inertia towards moving to a digestible Ca system in the diet formulation of broiler chickens until recently ( Walk et al, 2021 ), and the relatively cheaper cost of supplementing Ca via inorganic sources such as limestone as compared to inorganic P sources. To the authors' knowledge, this study represents the first attempt to determine the digestible Ca equivalency of phytase by employing varying concentrations of limestone in a similar manner to the use of graded inorganic P in deriving the P equivalence of phytase ( Jendza et al, 2006 ; Zhang et al, 2022 ). One limitation in the current study, possibly contributing to the observed low R -squared values in the regression equations, is the inability to match the range of digestible Ca resulting from feeding graded Ca levels from limestone with graded phytase supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there has been no attempt to estimate the digestible Ca equivalency of phytase relative to limestone in broiler chickens, which might be partly due to the seeming inertia towards moving to a digestible Ca system in the diet formulation of broiler chickens until recently ( Walk et al, 2021 ), and the relatively cheaper cost of supplementing Ca via inorganic sources such as limestone as compared to inorganic P sources. To the authors' knowledge, this study represents the first attempt to determine the digestible Ca equivalency of phytase by employing varying concentrations of limestone in a similar manner to the use of graded inorganic P in deriving the P equivalence of phytase ( Jendza et al, 2006 ; Zhang et al, 2022 ). One limitation in the current study, possibly contributing to the observed low R -squared values in the regression equations, is the inability to match the range of digestible Ca resulting from feeding graded Ca levels from limestone with graded phytase supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The regression equations for ileal digestible Ca on supplemental Ca or phytase were expressed by linear and nonlinear models, respectively ( Jendza et al, 2006 ; Zhang et al, 2022 ). The dependent variable (digestible Ca) was regressed against independent variables (calculated inorganic Ca from limestone or phytase intake).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation